Effective Strategies for Teaching Arabic with the Book Madarij Al-Durus Al-Arabiyah at Madrasah Assunniyyah Kencong Jember - Mannan, Ahmad Mizan Rosyadi Abdul Jalil; ., Zainuri; Azizah, Siti Rofiqotul (UAS PRESS, 2025)
In learning Arabic, maximum learning quality occupies a very urgent position in order to master Arabic and its learning components, which begin with basic knowledge of Arabic, especially for beginner classes. This research aims to describe the effectiveness of strategies using the book Madarij Al Durus Al Arabiyah to improve the quality of learning. This research uses a qualitative approach by collecting data through observation, interviews and documentation. The research results show that improving the quality of learning by using the book Madarij Al Durus Al Arabiyah can result in a good and appropriate duration of Arabic learning time, students are increasingly able to understand basic knowledge in Arabic and create active and conducive classes thereby increasing students' comfort in learning. . This strategy can be used as supporting material for teaching and learning Arabic to improve the quality of learning.